Implications of Lifestyle Factors and Polygenic Risk Score for Absolute Risk Prediction of Colorectal Neoplasm and Risk-Adapted Screening - Chen, Hongda; Liu, Li; Lu, Ming; Zhang, Yuhan; Lu, Bin; Zhu, Ying; Tian, Jianbo; Li, Xinying; Nie, Shaofa; Miao, Xiaoping; Dai, Min (Frontiers in Molecular Biosciences, 2021)
Background: Estimation of absolute risk of developing colorectal neoplasm are essential for personalized colorectal cancer (CRC) screening. We developed models to determine relative and absolute risk of colorectal neoplasm based on lifestyle and genetic variants, and to validate its application in risk-adapted screening. Methods: We prospectively collected data from 203 advanced neoplasms, 464 non-advanced adenomas and 1213 healthy controls from a CRC screening trial in China in 2018-2019. Risk prediction model based on 4 lifestyle factors and polygenic risk score (PRS) consisted of 19 CRC-associated single-nucleotide polymorphisms were developed. We assessed the relative and 10-year absolute risk of developing colorectal neoplasm, and the yield of a risk-adapted screening approach incorporating risk models, fecal immunochemical test and colonoscopy. Results: Compared to the participants with favorable lifestyle and lower PRS, those with unfavorable lifestyle and higher PRS had 2.87- and 3.79-fold higher risk of colorectal neoplasm in male and female, respectively. For a 50-year-old man or a 50-year-old women with the highest risk profile, the estimated 10-year absolute risk of developing colorectal neoplasm was 6.59% (95% CI: 6.53%-6.65%) and 4.19% (95% CI: 4.11%-4.28%), respectively; compared to 2.80% (95% CI: 2.78%-2.81%) for men and 2.24% (95% CI: 2.21%-2.27%) for women with lowest risk profile. The positive predictive value for advanced neoplasm was 31.7% and the number of colonoscopies needed to detect one advanced neoplasm was 3.2. Conclusion: The risk models, absolute risk estimates and risk-adapted screening presented in our study would contribute to develop effective personalized CRC prevention and screening strategies.